E-057 Validation that CBV can replace diffusion MRI in LVO patients with good aspect score. (22nd July 2018) - Moon, B
Abstract : Introduction: In large vessel occlusion patients, 'Time is Brain' is very important slogan. Saving time is one of the goals everyone wants. Therefore, we would like to perform thrombectomy in a short time using ASPECT score. However, the ASPECT score is insufficient, so we will try perfusion CT or diffusion MRI. But it can be a waste of time to do all the tests. So we need to try to reduce one of them. Our institution used low CBV volume and low CBF of perfusion CT to confirm diffusion-perfusion mismatch. For this purpose, we compared the low CBV volume with the diffusion restricted volume to confirm the matching between the two groups. Method and material: We retrospectively studied patients who had recanalization therapy with Large Vessel Occlusion (LVO, ICA or MCA (M1)) of anterior circulation at our hospital from 2011 to 2015. The cerebrovascular accident (CVA) protocol was activated when LVO was suspected, and non-enhance CT, perfusion CT, and CT angiography were performed. The CVA CT scan takes a 7 min. Among patients with LVO who visited our institution, we selected patients with a score of 7 or higher. In these patients, 10 areas such as ASPECT score were designated and scores were given to the lowered areas of CBF, MTT, and CBV compared with the contralateral side, and scoring was performed at 10 points. In the subsequent diffusion MRI, scoring system was applied in the same way. CBV scoring and diffusion scoring were compared to confirm schematic similarity. Results: In total, 78 patients met the inclusion criteria of this study. The difference between diffusion points and CBV points was divided into 0, 1, 2 or more. There were 23 patients with no difference, 39 patients with 1 point difference, 12 patients with 2 points difference, and 4 patients with more difference. Only 79.48% of the patients had a difference of 0 and 1 between the two points. Including the 2 point difference, the patients were 94.87%. Conclusion: The use of CBV to identify the diffuse restricted volume in the LVO patients with good ASPECT score seems to be a suitable and useful tool. Disclosures: B. Moon: None.